Challenges that face cultural tourism in post-conflict regions: The case of Kurdistan - Kadhim Magdid Braim; Scott McCabe; Jillian Rickly; Mohamed Gadi (European Regional Science Association (ERSA), 2016)
Tourism has multiple economic benefits for host countries that receive tourists. Policy makers are becoming more and more aware of the importance that appropriate tourism management has to maximise the benefits that tourism flows can bring. However, many developing countries suffer from a lack of an integrated tourism policy. Particular issues are faced in those countries that are dealing with local conflicts (sometimes over many years). These countries often lack investment in tourism resources even though they might have a huge potential and are rich in heritage and cultural assets. Conflict always changes the priorities of nations, and poses many challenges to the policy, and management for developing tourism as a viable economic sector. Post-conflict areas have barriers to tourism development, such as poor or damaged infrastructure, lack of services, low investment, political instability, a need to maximize revenue income, and the lack of planned tourism management. A current example of such a conflict area is Kurdistan. In 2013, the number of tourists were 2,952 027, yet in 2014 and 2015 the number had decreased to 1529434 and 1117501 respectively (General Board of Tourism, Kurdistan Regional Government, 2016). In addition, as a result of popular uprisings that occurred across the Middle East, there was a decline of 8% in tourism growth in these destination regions during 2011 (UNWTO, 2012). There is much research about cultural tourism management issues, challenges, sustainability, but there is a lack of studies undertaken to know how post-conflict issues interact or change or the effects of emergent situations on cultural and heritage tourism planning and management. Kurdistan, which is largely defined as a northern region of modern Iraq, can be considered one of the longest conflict areas since the end of World War 1, and has suffered from neglect of investment in its economic infrastructure over many decades. After the new Kurdistan self-governing region was recognised officially by the Iraqi government in 2003, there has been a sharp increase in the number of tourism arrivals, in particular, in last ten years, due to its location, climate and heritage. Tourism is seen as an important economic sector in Kurdistan and specifically leisure tourism. However, there is still wide scope to increase tourism in Kurdistan based on its diversity of cultures and cultural heritage sites. The UN World Tourism Organization estimated that cultural tourism currently accounts for 37% of the aggregate tourism in the world (Boyd, 2002; McKercher and Cross, 2002). Such potentially profitable tourism resources in Kurdistan has been neglected so far for the purpose of tourism. This paper aims to fill this gap and explore potentials and issues for developing cultural tourism in post conflict areas and in new autonomous regions such as Kurdistan, and to understand what cultural tourist strategy should be designed and implemented to develop tourism sector in Kurdistan to be successful, competitive and sustainable. By looking of the perspective of different stakeholders in Kurdistan, the study can understand the challenges and opportunities in developing cultural tourism in post conflict areas. The paper reports data from a series of focus groups conducted with residents and tourist, and in-depth interviews with policy makers and tourism experts in Erbil, Kurdistan, in 2015.
Keywords: 330